Structural packaging foams prepared by uni-directional freezing of paper sludge cellulose nanofibres and poly (vinyl alcohol). - Adu, Cynthia; Rahatekar, Sameer S.; Filby, Jyoti; Ayre, David; Jolly, Mark R. (Cranfield University, 2019)
This dataset contains results from the experimental tests on cellulose nanofibres and polyvinyl alcohol foams prepared by uni-directional freezing. The compression tests of 8 samples are recorded here with their stress-strain curves plotted. Additional parameters of the foams such as density, volume, porosity are also recorded.
Keywords: 'Cellulose nanofibres'; 'Aerogel'; 'Foam'; 'Ice-templating'; 'Biomaterials'